Chemical composition and in vitro digestibility of silages of taro (Colocasia esculenta (L.) Schott) tubers for feeding pigs - Caicedo, W.; Rodríguez, R.; Lezcano, P.; Ly, Julio; Valle, S.; Flores, L.; Ferreira, F. N. A. (Cuban Journal of Agricultural Science, 2016)
To assess chemical composition and in vitro digestibility of silages of taro tubers (Colocasia esculenta (L.) Schott), for feeding pigs, four silages with waste tubers were carried out. A completely randomized design with a 4x6 factorial arrangement to analyze the chemical composition was applied. Natural yogurt (-1NY), whey (-2W), whey with 5%of molasses (-3WM5) and whey with 10% of molasses (-4WM10) were evaluated as silage components. The silages time were 0, 15, 30, 60, 90 and 180 days. The in vitro digestibility of DM and OM with 15d of silages elaboration was investigated by means of simple classification design. The interactions treatments per day were significant (P < 0.05).The silage four in the 180th day show higher DM content (33.61%).The highest CP(N x 6.25) concentration(8.83%) was evidenced in silage two, in the 90th day. The lowest CF was determined in silage two in the 0 (2.85) and 60th (2.84) days. The GE was high in silage one in the 0 day (4.40 kcal g DM-1).The highest in vitro digestibility coefficient of DM (74.65 %) and OM (76.76 %) was found in silage two. The conservation of taro tubers, between 0 and 180 d, by means of the addition of variables levels of natural yogurt, whey and sugar cane molasses, create different products with good DM, CP, GE content and low CF concentration, capable to be used in feeding pigs. Key words: by-products, fermentation, digestibility, preservation